<h2>SOLVING</h2>
![\Large\maltese\underline{\textsf{A. What is Asked}}](https://tex.z-dn.net/?f=%5CLarge%5Cmaltese%5Cunderline%7B%5Ctextsf%7BA.%20What%20is%20Asked%7D%7D)
What is the slope of the line passing through the point (1,2) and (5,4)
![\Large\maltese\underline{\textsf{This problem has been solved!}}](https://tex.z-dn.net/?f=%5CLarge%5Cmaltese%5Cunderline%7B%5Ctextsf%7BThis%20problem%20has%20been%20solved%21%7D%7D)
Formula used, here ![\bf{\dfrac{y2-y1}{x2-x1}](https://tex.z-dn.net/?f=%5Cbf%7B%5Cdfrac%7By2-y1%7D%7Bx2-x1%7D)
_______________________________________________________
| simplify
| reduce
![\bf{\dfrac{1}{2}](https://tex.z-dn.net/?f=%5Cbf%7B%5Cdfrac%7B1%7D%7B2%7D)
![\rule{300}{1.7}](https://tex.z-dn.net/?f=%5Crule%7B300%7D%7B1.7%7D)
![\bf{Result:}](https://tex.z-dn.net/?f=%5Cbf%7BResult%3A%7D)
![\bf{=Slope:\dfrac{1}{2}](https://tex.z-dn.net/?f=%5Cbf%7B%3DSlope%3A%5Cdfrac%7B1%7D%7B2%7D)
![\boxed{\bf{aesthetic\not101}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cbf%7Baesthetic%5Cnot101%7D%7D)
#1)
Answer:
x=1 and y=12
Explanation:
y=5x+7
y=2x+10
This system should use substitution because the value of y is given in terms if x.
Substitution:
5x+7=2x+10
Solve:
3x=3
x=1
Substitute x to solve for y by plugging x into one if the original equations(doesn’t matter which one is used).
y=5x+7
y=5(1)+7
y=5+7
y=12
#2)
Answer:
x=-8 and y=2
Explanation:
y=2x+18
9y=-2x+2
This system also uses substitution. The value of y us already given in terms if c in the first equations, so we will substitute in the second equation.
Substitute:
9(2x+18)=-2x+2
Solve:
18x+162=-2x+2
20x=-160
x=-8
Now that we have the value if x, plug it into one of the original equations(doesn’t matter which equation) and substitute to find y.
y=2x+18
Substitute:
y=2(-8)+18
Solve:
y=-16+18
y=2
1964.16 is hundredth
1964.2 is tenth
1964 is one
1960 is ten
2000 is hundred
Answer:
Step-by-step explanation:
![y^2-11y+n\\=(y-(11/2))^2+n-(11/2)^2](https://tex.z-dn.net/?f=y%5E2-11y%2Bn%5C%5C%3D%28y-%2811%2F2%29%29%5E2%2Bn-%2811%2F2%29%5E2)
So in order the trinomial a perfect square we need
![n-(11/2)^2 =0\\n= (11/2)^2\\n=\frac{121}{4}](https://tex.z-dn.net/?f=n-%2811%2F2%29%5E2%20%3D0%5C%5Cn%3D%20%2811%2F2%29%5E2%5C%5Cn%3D%5Cfrac%7B121%7D%7B4%7D)
When n is equal to this number that we have
![y^2-11y+n = (y- (11/2))^2](https://tex.z-dn.net/?f=y%5E2-11y%2Bn%20%3D%20%28y-%20%2811%2F2%29%29%5E2)
Answer:
how to what? I don't understand